Bent-tailed radio sources in the Australia telescope large area survey of the Chandra deep field south - Dehghan, S.; Johnston-Hollitt, M.; Franzen, Thomas; Norris, R.; Miller, N. (IOP, 2014)
Using the 1.4 GHz Australia Telescope Large Area Survey, supplemented by the 1.4 GHz Very Large Array images, we undertook a search for bent-tailed (BT) radio galaxies in the Chandra Deep Field South. Here we present a catalog of 56 detections, which include 45 BT sources, 4 diffuse low-surface-brightness objects (1 relic, 2 halos, and 1 unclassified object), and a further 7 complex, multi-component sources. We report BT sources with rest-frame powers in the range 1022 ≤ P 1.4 GHz ≤ 1026 W Hz–1, with redshifts up to 2 and linear extents from tens of kiloparsecs up to about 1 Mpc. This is the first systematic study of such sources down to such low powers and high redshifts and demonstrates the complementary nature of searches in deep, limited area surveys as compared to shallower, large surveys. Of the sources presented here, one is the most distant BT source yet detected at a redshift of 2.1688. Two of the sources are found to be associated with known clusters: a wide-angle tail source in A3141 and a putative radio relic which appears at the infall region between the galaxy group MZ 00108 and the galaxy cluster AMPCC 40. Further observations are required to confirm the relic detection, which, if successful, would demonstrate this to be the least powerful relic yet seen with P 1.4 GHz = 9 × 1022 W Hz–1. Using these data, we predict future 1.4 GHz all-sky surveys with a resolution of ~10 arcsec and a sensitivity of 10 μJy will detect of the order of 560,000 extended low-surface-brightness radio sources of which 440,000 will have a BT morphology.